Emotional exhaustion and workload predict clinician-rated and objective patient safety - Welp, Annalena; Meier, Laurenz L.; Manser, Tanja (Frontiers in Psychology, 2015)
Aims: To investigate the role of clinician burnout, demographic and organizational characteristics in predicting subjective and objective indicators of patient safety. Background: Maintaining clinician health and ensuring safe patient care are important goals for hospitals. While these goals are not independent from each other, the interplay between clinician psychological health, demographic and organizational variables and objective patient safety indicators is poorly understood. The present study addresses this gap. Method: Participants were 1425 physicians and nurses working in intensive care. (Multilevel) regression analysis was used to investigate the effect of burnout as an indicator of psychological health, demographic (e.g., professional role and experience) and organizational (e.g., workload, predictability) characteristics on standardized mortality ratios, length of stay and clinician-rated patient safety. Results: Clinician-rated patient safety were associated with burnout, trainee status, and professional role. Mortality was predicted by emotional exhaustion. Length of stay was predicted by workload. Contrary to our expectations, burnout did not predict length of stay, and workload and predictability did not predict standardized mortality ratios. Conclusion: At least in the short-term, clinicians seem to be able to maintain safety despite high workload and low predictability. Nevertheless, burnout poses a safety risk. Subjectively, burnt-out clinicians rated safety lower, and objectively, units with high emotional exhaustion had higher standardized mortality ratios. In summary, our results indicate that clinician psychological health and patient safety could be managed simultaneously. Further research needs to establish causal relationships between these variables or and support the development of managerial guidelines to ensure clinicians’ psychological health and patients’ safety.